Correlation of food handling practices of vendors in Pasig City Mega Market on microbiological quality of ready-to-eat Filipino steamed rice cakes - Javinal, Elaine Rizza P.
There are existing correlation studies regarding the handling practices and the microbial quality of Filipino foods, however, there is a limited number of existing studies for ready-to-eat (RTE) Filipino steamed rice cakes sold in public markets. Food safety handling practices are crucial to study because inadequacy of these may contribute to foodborne outbreaks. Hence, this study aimed to assess the correlation between food handling practices of Pasig City Mega Market vendors (n=15) and the microbiological quality of RTE Filipino steamed rice cakes or puto. Results showed that the food handling practices of the puto vendors were very good (mean of 12 points). However, some observations deviated from the self-reported handling practices of the vendors which suggest that improvements regarding standard practices should be made. Physicochemical properties (pH: 4.82 ± 0.20 to 5.91 ± 0.14; aw: 0.94 ± 0.00 to 0.97 ± 0.01) and microbiological quality of the puto samples (APC: 8.37-12.7 log CFU/g; YMC: 9.47-10.60 log CFU/g; and E. coli count: <1.8 - 3.15 MPN/g) were also determined, which reflects the prior observation as these values are higher than standards and related studies. Results showed substantial and low positive correlation, obtaining values of -0.62 (APC) and -0.18 (E. coli count) respectively, and a low positive correlation of 0.15 (YMC). Based on the results, puto vendors need proper guidance on food safety practices to ensure product safety and hygiene.